2022
DOI: 10.1038/s41598-022-05259-y
|View full text |Cite
|
Sign up to set email alerts
|

CD97 is associated with mitogenic pathway activation, metabolic reprogramming, and immune microenvironment changes in glioblastoma

Abstract: Glioblastoma (GBM) is the most common primary brain tumor with a median survival under two years. Using in silico and in vitro techniques, we demonstrate heterogeneous expression of CD97, a leukocyte adhesion marker, in human GBM. Beyond its previous demonstrated role in tumor invasion, we show that CD97 is also associated with upregulation of the mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/Erk) and phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) pathways in GBM. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The results showed that in the LGG, ADGRE5 was significantly positively correlated with NK CD56dim cells, T cells, macrophages, neutrophils, eosinophils, cytotoxic cells, aDC, Th17 cells, iDC, Th2 cells, DC, T helper cells, B cells, Th1 cells, and mast cells and negatively correlated with pDC and Tcm. This is consistent with the results of Safaee et al, who found that the expression of non-polarized M0 macrophages, immunosuppressive Treg cells, and resting NK cells increased in glioma cells with high ADGRE5 expression [ 37 ]. Under UVM, ADGRE5 was significantly positively correlated with Th2 cells, aDC, Th1 cells, eosinophils, TFH, NK CD56dim cells, Tgd, T cells, cytotoxic cells, macrophages, T helper cells, neutrophils, DC, B cells, and iDC and negatively correlated with Th17 cells and pDC.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that in the LGG, ADGRE5 was significantly positively correlated with NK CD56dim cells, T cells, macrophages, neutrophils, eosinophils, cytotoxic cells, aDC, Th17 cells, iDC, Th2 cells, DC, T helper cells, B cells, Th1 cells, and mast cells and negatively correlated with pDC and Tcm. This is consistent with the results of Safaee et al, who found that the expression of non-polarized M0 macrophages, immunosuppressive Treg cells, and resting NK cells increased in glioma cells with high ADGRE5 expression [ 37 ]. Under UVM, ADGRE5 was significantly positively correlated with Th2 cells, aDC, Th1 cells, eosinophils, TFH, NK CD56dim cells, Tgd, T cells, cytotoxic cells, macrophages, T helper cells, neutrophils, DC, B cells, and iDC and negatively correlated with Th17 cells and pDC.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the MAPK signaling pathway, past research on CD97 has identified other signaling mechanisms, including G protein-mediated Gα i (reduces cyclic-AMP) and Gα 12/13 (activates RHOA) activation and PI3K/AKT pathway activation ( Figure 5A ). 27 , 31 , 51 , 52 We investigated whether CD97 influenced these other signaling pathways in our PDGCs. CD97 overexpression in our PDGCs did not alter canonical G protein-mediated signaling as measured by luciferase reporter assays ( Figure S4B ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the MAPK signaling pathway, past research on CD97 has identified other signaling mechanisms, including G protein-mediated Gα i (reduces cyclic-AMP) and Gα 12/13 (activates RHOA) activation, and PI3K/AKT pathway activation ( Figure 5A ). 27,31,51,52 We investigated whether CD97 influenced these other signaling pathways in our PDGCs. CD97 overexpression in our PDGCs did not alter canonical G protein-mediated signaling as measured by luciferase reporter assays ( Supp.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28] CD97 expression in GBM was first demonstrated in 2012, when it was found to confer a migratory phenotype. 33 More recent work has also implicated CD97 in cellular proliferation, GBM stem cell self-renewal, and tumor metabolism, [29][30][31][32] but the underlying mechanisms have not been elucidated. Here, we have taken a methodical approach to characterize the oncogenic function of CD97 in GBM using PDGCs from all TCGA-defined transcriptional subtypes (proneural, classical, mesenchymal) and advanced genetic, transcriptomic, metabolomic, cellular, and biochemical approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation